Kepemimpinan Transformasional Kepala Madrasah dalam Meningkatkan Kinerja Guru di MA Al-Iman Bulus Kecamatan Gebang Kabupaten Purworejo - Muhamad Ghufron; Eliyanto Eliyanto (LPPM IAINU Kebumen, 2020)
The leadership of the Madrasah Principal is one of the factors that influence teacher performance improvement. Madrasah heads through transformational leadership are expected to be able to improve teacher performance at MA Al-Iman Bulus Gebang Purworejo. This study aims to determine the behavior of the madrasa head in improving the performance of MA Al-Iman Bulus Gebang Purworejo teachers, especially transformative behavior in their leadership. This research was conducted with a qualitative approach. The subjects of this study were school principals, teachers and students. Data collection techniques from this study used observation, interviews, and documentation. The results of this study indicate that the head of MA Al Iman Bulus Gebang Purworejo has implemented the four dimensions of transformational leadership. This is evidenced by the results of the study, namely: 1) the Madrasah Head provides ideal influence; 2) The Head of Madrasah provides motivation that inspires teachers in improving teacher performance at MA Al-Iman Bulus Gebang Purworejo; 3) The head of the Madrasah provides scientific stimulation to the teacher so that the performance of the MA Al Iman Bulus Gebang Purworejo teacher increases; 4) The head of the Madrasah as a leader pays close attention to individual teachers so that the performance of MA Al-Iman Bulus Gebang Purworejo teachers is increasing.